PSIKOEDUKASI: MENGENGAL SELF EFFICACY UNTUK BIJAK BER-AI DENGAN KOMUNIKASI CONFIRMATORY FEEDBACK - Ayu Laksita Utami; Chairunissa; Ega Abinowo Herlambang; Evi Santi Pratiwi; Muhammad Hafizh Syahri (CV. ADIBA AISHA AMIRA, 2025)
Low self-efficacy is a massive problem among Indonesian teenagers and can affect mental health. Meanwhile, the unwise use of AI will have a worse impact if not handled properly. Psychoeducation: Getting to Know Self-Efficacy for Wise AI with Confirmatory Feedback Communication aims to increase self-efficacy and awareness of the wise use of AI technology among students of SMK Negeri 67 Jakarta. Using the confirmatory feedback approach, this psychoeducational activity was carried out through a series of pre-tests, providing materials, discussions in small groups to confirm participants' views, and post-tests. The results of the analysis showed that an increase in the score of reflective attitudes towards the use of AI was influenced by the score of increasing self-efficacy. This psychoeducation shows that the higher the self-efficacy, the use of AI tends to decrease in the data. The confirmatory feedback approach can also be an educational strategy that supports independent and ethical learning in the digital era.